1983
DOI: 10.1099/00221287-129-2-367
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelation Of Phototaxis, Membrane Potential And K+/Na+ Gradient In Halobacterium Halobium

Abstract: The attractant effect of green light and the repellent effect of blue light on Halobacterium halobium were studied. It was found that addition of CNand dicyclohexylcarbodiimide, which block the redox chain and H+-ATPase, respectively, increased both the amplitude of lightdependent changes of membrane potential (A$), monitored by the distribution of tetraphenylphosphonium, and the sensitivity of the green-light taxis. A direct proportionality between A$ and the green-light sensitivity was revealed. The sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The previous results obtained in our group have shown that DCCD and cyanide, the inhibitors of light-independent A/2H generators in H. halobium strongly increased the sensitivity of the cells to the attractant effect of the long wavelength light [8,9]. This fact was interpreted as indicating a A/2H-dependent mechanism of reception in the green light response.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…The previous results obtained in our group have shown that DCCD and cyanide, the inhibitors of light-independent A/2H generators in H. halobium strongly increased the sensitivity of the cells to the attractant effect of the long wavelength light [8,9]. This fact was interpreted as indicating a A/2H-dependent mechanism of reception in the green light response.…”
Section: Resultsmentioning
confidence: 75%
“…40% decrease in the light intensity by a neutral filter was used as a stimulus. Additions: 0.1 mM DCCD and 1 mM NaCN bacteria in a A/~H-dependent manner [9]. The studies on various species of bacteria demonstrated that aerotaxis and A/~H reception were controlled by similar, if not identical, mechanisms [14,15].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…This function is related to the proton-translocating activity of bacteriorhodopsin (7-10), and it has been suggested that receptor function is mediated by a device that monitors electrochemical gradient of hydrogen ions across the membrane (⌬ H ϩ) called a protometer (5,6,10,15,35). This supports other data on the photoreceptory function of bacteriorhodopsin which also attributed the effects of bacteriorhodopsin on swimming behavior to a secondary consequence of electrogenic proton pumping on metabolic or signal-transducing pathways rather than to primary sensory signaling such as that mediated by sRI (46).…”
mentioning
confidence: 99%